Targeting M2 Macrophages with a Novel NADPH Oxidase Inhibitor - Sébastien Dilly; Miguel Romero; Stéphanie Solier; Olivier Feron; Chantal Dessy; Anny Slama Schwok (MDPI AG, 2023)
ROS in cancer cells play a key role in pathways regulating cell death, stemness maintenance, and metabolic reprogramming, all of which have been implicated in resistance to chemo/ immunotherapy. Adjusting ROS levels to reverse the resistance of cancer cells without impairing normal cell functions is a new therapeutic avenue. In this paper, we describe new inhibitors of NADPH oxidase (NOX), a key enzyme in many cells of the tumor microenvironment. The first inhibitor, called Nanoshutter-1, NS1, decreased the level of tumor-promoting "M2" macrophages differentiated from human blood monocytes. NS1 disrupted the active NADPH oxidase-2 (NOX2) complex at the membrane and in the mitochondria of the macrophages, as shown by confocal microscopy. As one of the characteristics of tumor invasion is hypoxia, we tested whether NS1 would affect vascular reactivity by reducing ROS or NO levels in wire and pressure myograph experiments on isolated blood vessels. The results show that NS1 vasodilated blood vessels and would likely reduce hypoxia. Finally, as both NOX2 and NOX4 are key proteins in tumors and their microenvironment, we investigated whether NS1 would probe these proteins differently. Models of NOX2 and NOX4 were generated by homology modeling, showing structural differences at their C-terminal NADPH site, in particular in their last Phe. Thus, the NADPH site presents an unexploited chemical space for addressing ligand specificity, which we exploited to design a novel NOX2-specific inhibitor targeting variable NOX2 residues. With the proper smart vehicle to target specific cells of the microenvironment as TAMs, NOX2-specific inhibitors could open the way to new precision therapies.